TABLE OF CONTENTS - Faculty of Education, Editorial Board (Ilorin Journal of Education, 2025)
The articles in this edition contain theoretical and empirical papers covering a broad range of innovative issues in teaching and learning processes and educational research. The edition is borne out of the need to address the gap in innovative educational research, providing the best to scholars. The articles were well-written by experienced scholars from within and outside the country. This edition with its international outlook, serves as a valuable research resource in the teaching and learning process by providing readers with scientific knowledge through the well-researched articles in this edition. We are therefore pleased to present this edition of Ilorin Journal of Education (IJE) for your reading and knowledge acquisition.